Targeted Re-Sequencing Approach of Candidate Genes Implicates Rare Potentially Functional Variants in Tourette Syndrome Etiology - Alexander, John; Potamianou, Hera; Xing, Jinchuan; Deng, Li; Karagiannidis, Iordanis; Tsetsos, Fotis; Drineas, Petros; Tarnok, Zsanett; Rizzo, Renata; Wolanczyk, Tomasz; Farkas, Luca; Nagy, Peter; et al. (Frontiers in Neuroscience, 2016)
Although the genetic basis of Tourette Syndrome (TS) remains unclear, several candidate genes have been implicated. Using a set of 382 TS individuals of European ancestry we investigated four candidate genes for TS (HDC, SLITRK1, BTBD9 and SLC6A4) in an effort to identify possibly causal variants using a targeted re-sequencing approach by next generation sequencing technology. Identification of possible disease causing variants under different modes of inheritance was performed using the algorithms implemented in VAAST. We prioritized variants using Variant ranker and validated five rare variants via Sanger sequencing in HDC and SLITRK1, all of which are predicted to be deleterious. Intriguingly, one of the identified variants is in linkage disequilibrium with a variant that is included among the top hits of a genome-wide association study tolerance to citalopram treatment, an antidepressant drug with off-label use also in obsessive compulsive disorder. Our findings provide additional evidence for the implication of these two genes in TS susceptibility and the possible role of these proteins in the pathobiology of TS should be revisited.